Pengaruh Model Pembelajaran Auditory Intellectually Repetition Berbantuan Wordwall Terhadap Kemampuan Berpikir Kritis Matematis Siswa - Ilyani Anis; Nuraina Nuraina; Haves Qausar (Jurnal Ilmiah Kanderang Tingang, 2026)
Students’ critical thinking skills in mathematics remain relatively underdeveloped. This is due to their tendency to approach problems from only one perspective, which limits their ability to evaluate and select effective solutions. Therefore, innovative and varied learning models are needed to foster these skills, one of which is the Auditory Intellectually Repetition (AIR) learning model. This study aims to determine the effect of the AIR learning model assisted by Wordwall on students’ mathematical critical thinking skills. The research employed a quasi-experimental design with a nonequivalent posttest-only control group. The population consisted of eighth-grade students at UPTD SMP Negeri 2 Gandapura. Saturated sampling was used, with class VIII-B assigned as the experimental group and class VIII-A as the control group. Data were collected through a post-test to measure students’ mathematical critical thinking skills and were analyzed using an independent samples t-test with the aid of SPSS version 25, at a 5% significance level. The results showed a significance value (Sig. 2-tailed) of 0.028 < 0.05. Therefore, it can be concluded that the AIR learning model supported by Wordwall has a significant effect on students’ mathematical critical thinking skills in mathematics learning.